Evaluasi Peresepan Pada Pasien Rawat Jalan Geriatri Hipertensi Berdasarkan Beers Criteria Poli Penyakit Dalam Di RSUD dr. Soekardjo Kota Tasikmalaya - Nabilah Nabilah; Kamiel Roesman Bachtiar; Eddy Suhardiana (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Hypertension is a condition that experiences an abnormal increase in blood pressure, the elderly are said to be hypertensive if their blodd pressure reaches ≥130/80 mmHg and is a non-communicable disease. A study has been carried out regarding the Evaluation of Prescribing in Outpatient Geriatric Hypertension Based on the Beers Criteria for Internal Medicine at RSUD dr. Soekardjo City of Tasikmalaya using a descriptive method of retrospective medical record data of hypertensive geriatric patients. This study aims to determine the treatment profile and the percentage of drug use included in the 2019 beers criteria list. The results showed that the most commonly prescribed treatment combination in this study was the combination of the ACE Inhibitor drug class (Ramipril) and the CCB drug group (Amlodipine), and Inappropriate drug prescribing in geriatric patients with hypertension in the outpatient installation of RSUD dr. Soekardjo City of Tasikmalaya in the 2020 period is still high with the number of inappropriate prescriptions as many as 47 (67,1%) prescriptions classified as PIMs (Potentially Inappropriate Medication). So it can be concluded that the high mismatch of therapy can be caused becaused because patients receive more than one drug that is not suitable for geriatric when getting drug prescriptions and to reduce these incidents it can be done by increasing the selection os safe drugs in geriatric using the 2019 beers criteria